Magneto-optical studies of Gd-implanted GaN: No spin alignment of conduction band electrons - Buß, J. H.; Rudolph, J.; Shvarkov, S.; Semond, F.; Reuter, Dirk; Wieck, A. D.; Hägele, D. (Applied Physics Letters)

The effect of (NH4)2Sxpassivation on the (311)A GaAs surface and its use in AlGaAs/GaAs heterostructure devices - Carrad, D J; Burke, A M; Reece, P J; Lyttleton, R W; Waddington, D E J; Rai, A; Reuter, Dirk; Wieck, A D; Micolich, A P (Journal of Physics: Condensed Matter)

Spin relaxation length in quantum dot spin LEDs - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (physica status solidi (c))

Frequency-Stabilized Source of Single Photons from a Solid-State Qubit - Prechtel, Jonathan H.; Kuhlmann, Andreas V.; Houel, Julien; Greuter, Lukas; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Physical Review X)

Biexcitons in semiconductor quantum dot ensembles - Moody, Galan; Singh, Rohan; Li, Hebin; Akimov, Ilya A.; Bayer, Manfred; Reuter, Dirk; Wieck, Andreas D.; Bracker, Allan S.; Gammon, Daniel; Cundiff, Steven T. (physica status solidi (b))

High-resolution mass spectrometer for liquid metal ion sources - Wortmann, Martin; Ludwig, Arne; Meijer, Jan; Reuter, Dirk; Wieck, Andreas D. (Review of Scientific Instruments)

Charge noise and spin noise in a semiconductor quantum device - Kuhlmann, Andreas V.; Houel, Julien; Ludwig, Arne; Greuter, Lukas; Reuter, Dirk; Wieck, Andreas D.; Poggio, Martino; Warburton, Richard J. (Nature Physics)

A dark-field microscope for background-free detection of resonance fluorescence from single semiconductor quantum dots operating in a set-and-forget mode - Kuhlmann, Andreas V.; Houel, Julien; Brunner, Daniel; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Review of Scientific Instruments)

Software Engineering for Self-Adaptive Systems: A Second Research Roadmap - de Lemos, Rogrio; Giese, Holger; A. Müller, Hausi; Shaw, Mary; Andersson, Jesper; Litoiu, Marin; Schmerl, Bradley; Tamura, Gabriel; M. Villegas, Norha; Vogel, Thomas; Weyns, Danny; Baresi, Luciano; et al. (Software Engineering for Self-Adaptive Systems II)

Leichtgewichtige Traceability im agilen Entwicklungsprozess am Beispiel von Scrum - Bouillon, Elke; Güldali, Baris; Herrmann, Andrea; Keuler, Thorsten; Moldt, Daniel; Riebisch, Matthias (Softwaretechnik-Trends)

Testen bei Migrationsprojekten - Grieger, Marvin; Güldali, Baris; Sauer, Stefan; Mlynarski, Michael (OBJEKTspektrum (Online Themenspecials))

Maßgeschneidert und werkzeugunterstützt Entwickeln angepasster Requirements Engineering-Methoden - Fazal-Baqaie, Masud; Güldali, Baris; Luckey, Markus; Sauer, Stefan; Spijkerman, Michael (OBJEKTspektrum (Online Themenspecials))

Editorial - Engels, Gregor; Luckey, Markus (Computer Science - Research and Development)

Informationstechnik spart Ressourcen - Engels, Gregor; Gerth, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Müller, Wolfgang; Sauer, Stefan (Forschungsforum Paderborn)

Detection and Resolution of Conflicting Change Operations in Version Management of Process Models - Gerth, Christian; Küster, Jochen; Luckey, Markus; Engels, Gregor (Software and Systems Modeling)

Wirtschaftlichkeitsberechnung für MBT: Wann sich modellbasiertes Testen lohnt - Faragó, David; Törsel, Arne-Michael; Mlynarski, Michael; Weißleder, Stephan; Güldali, Baris; Brandes, Christian (OBJEKTspektrum)
Modellbasiertes Testen verspricht potenziell eine höhere Effizienz und Effektivität im Testprozess. Ob im eigenen Kontext der Einsatz wirtschaftlich ist, ist jedoch häufig unklar. Dieser Beitrag analysiert systematisch Kosten- und Nutzenfaktoren und stellt ein Verfahren zur Abschätzung der Wirtschaftlichkeit des modellbasierten Testens vor. Anhand eines Beispiels wird der Ablauf veranschaulicht.

Spin injection, transport, and relaxation in spin light-emitting diodes: magnetic field effects - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Spintronics VI)

Spin relaxation length in quantum dot spin LEDs - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (physica status solidi (c))

Influence of recombination center interaction on the photoluminescence of AlGaAs/GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Hanle effect in (In,Ga)As quantum dots: Role of nuclear spin fluctuations - Kuznetsova, M. S.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kavokin, K. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)